2013
DOI: 10.1111/jomf.12055
|View full text |Cite
|
Sign up to set email alerts
|

Does Child‐Care Quality Mediate Associations Between Type of Care and Development?

Abstract: Studies document that, on average, children cared for in centers, as compared to homes, have higher cognitive test scores but worse socioemotional and health outcomes. The authors assessed whether the quality of care received explains these associations. They considered multiple domains of child development—cognitive, socioemotional, and health—and examined whether mediation is greater when quality measures are better aligned with outcome domains. Using the Early Childhood Longitudinal Study Birth Cohort, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Such selection—which is really about what children are evoking from adults, not what they are actively choosing themselves—has been suggested before (Abner et al, 2013) but is insufficiently documented. The early education literature has long been concerned with selection effects, but children's own prior abilities have not been examined as a selection mechanism, one that could potentially explain observed preschool effects on children's achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such selection—which is really about what children are evoking from adults, not what they are actively choosing themselves—has been suggested before (Abner et al, 2013) but is insufficiently documented. The early education literature has long been concerned with selection effects, but children's own prior abilities have not been examined as a selection mechanism, one that could potentially explain observed preschool effects on children's achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ choice of preschool might be driven by children's academic skills, and the lack of attention to this potential for children to elicit more investment (compensatory or enriching) from parents has been identified as a limitation of the literature on the impact of preschool in children's school success (Abner, Gordon, Kaestner, & Korenman, 2013). Additionally, care-related changes in children's early competencies can elicit changes in parenting (Jaeger & Weinraub, 1990).…”
Section: Developmental Systems and Family-preschool-child Transactionsmentioning
confidence: 99%
“…Many studies have demonstrated that early language exposure predicts the size of children's growing vocabulary and later verbal skills and literacy skills (Huttenlocher et al 1991;Hurtado et al 2008), and centre-based child care has been associated with more advanced language development (NICHD ECCRN 2000;Fantuzzo et al 2005;Loeb et al 2007;Abner et al 2013). Moreover, peers can also affect development (Dunn 2004) by facilitating or necessitating greater language production.…”
Section: Discussionmentioning
confidence: 99%
“…In the decades since, promises of a national child care strategy have come on and off political agendas with few concrete results (Albanese, 2011a). Even when the discourse around child care shifted to a more child-centred social investment strategy, demonstrating the contribution of quality child care to child development, children's rights, and even economic development (see Abner, Gordon, Kaestner, & Korenman, 2013;Hübenthal & Ifland, 2011;Warner & Prentice, 2013), Canadians have seen few improvements in child care policy (Friendly, Beach, & Turiano, 2002;Friendly, Beach, Ferns, & Turiano, 2007;Friendly & Prentice, 2009; Organisation for Economic Cooperation and Development [OECD], 2004[OECD], , 2006Scherer, 2001). …”
Section: Child Care Policy In Canada Ontario and Quebecmentioning
confidence: 99%